The Effect of Group Counseling Services on the Dangers of Narcolema Among Adolescents Using the Self-Control Technique - Miranda, Ivo Liza; Siregar, Alfin (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
This study aims to evaluate the impact of group counseling services using self-control techniques on the dangers of narcolema (pornography addiction) among adolescents. The issue addressed is the high level of pornography addiction among teenagers, which poses significant risks to their physical, mental, and social well-being. The research utilized a quantitative approach with a "One Group Pretest-Posttest" experimental design. Data were collected through questionnaires and analyzed using paired sample t-test statistical analysis with the help of SPSS software. The results indicate that group counseling services employing self-control techniques significantly reduce narcolema addiction levels. The average pretest score of the subjects was 87.12 (very high category), which decreased to 71 (low category) in the posttest, showing a significant reduction of 17%. The self-control technique enables individuals to regulate behavior, cognition, and decision-making, helping adolescents reduce their access to pornographic content. In conclusion, group counseling services with self-control techniques are effective in reducing pornography addiction behaviors among adolescents. The implications of this study highlight the necessity of implementing group-based counseling services in schools to address negative behaviors related to technology use. This research also recommends active roles for parents and educational institutions in monitoring and providing appropriate interventions for adolescents to tackle challenges in the digital era.